IMPLEMENTATION OF THE TARGET COSTING METHOD IN AN EFFORT TO REDUCE COSTS - Bahri, Silvia Andriani (Proceeding International Seminar of Islamic Studies, 2023)
The costing method is a method that is appropriate and in line with the increase and competition in achieving the company's goals for cost reduction. The purpose of this study is to find out that the target costing approach can be used as a tool in efforts to reduce production costs to increase gross or gross profit. Target costing is a method of reducing production costs based on the selling price and expected profit. The type of research used is descriptive quantitative. Data collection methods used in this study were observation and interviews. The results show that the target costing method is very efficient to be applied in calculating production costs because it is based on a comparison of production costs and gross profit obtained using target costing and without target costing.